Positive SARS-CoV-2 detection on intraoperative nasopharyngeal viral testing is not associated with worse outcomes for asymptomatic elective surgical patients - Clancy, Paul W.; Knio, Ziyad O.; Zuo, Zhiyi (Frontiers in Medicine, 2022)
Background It has been demonstrated that surgical patients with COVID-19 are at increased risk for postoperative complications. However, this association has not been tested in asymptomatic elective surgical patients. Methods A retrospective cohort study among elective gynecological and spine surgery patients at a single tertiary medical center from July 2020 through April 2022 (n=1130) was performed. The primary endpoint was prolonged (> 75th percentile for the corresponding surgical service) length of stay. Secondary endpoints included postoperative respiratory complications, duration of supplemental oxygen therapy, and other major adverse events. The association between SARS-CoV-2 detection and the above outcomes was investigated with univariate and multivariable analyses. Findings Of 1130 patients who met inclusion criteria, 30 (2.7%) experienced intraoperative detection of SARS-CoV-2. Those with intraoperative viral detection did not experience an increased incidence of prolonged length of stay (16.7% vs 23.2%; RR, 0.72 [95% CI, 0.32 to 1.61]; P = 0.531) nor did they have a longer mean length of stay (4.1 vs 3.9 days; P = 0.441). Rates of respiratory complications (3.3% vs 2.9%; RR, 1.15 [95% CI, 0.16 to 8.11]; P = 0.594) and mean duration of supplemental oxygen therapy (9.7 vs 9.3 hours; P = 0.552) were similar as well. All other outcomes were similar in those with and without intraoperative detection of SARS-CoV-2 (all P > 0.05). Interpretation Asymptomatic patients with incidental detection of SARS-CoV-2 on intraoperative testing do not experience disproportionately worse outcomes in the elective spine and gynecologic surgical population.